2010
DOI: 10.1242/jcs.066464
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulates alveolar epithelial function by inducing Na+/K+-ATPase translocation to the plasma membrane in a process mediated by the action of Akt

Abstract: Stimulation of Na+/K+-ATPase translocation to the cell surface increases active Na+ transport, which is the driving force of alveolar fluid reabsorption, a process necessary to keep the lungs free of edema and to allow normal gas exchange. Here, we provide evidence that insulin increases alveolar fluid reabsorption and Na+/K+-ATPase activity by increasing its translocation to the plasma membrane in alveolar epithelial cells. Insulin-induced Akt activation is necessary and sufficient to promote Na+/K+-ATPase tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Examples include insulin-stimulated transport of GLUT4 glucose transporter-carrying vesicles to the plasma membrane to allow glucose to enter muscles and adipose tissues (Rowland et al, 2011;Taniguchi et al, 2006), increased cell surface expression of the Na + /K + ATPase to clear postprandial blood K + (Al-Khalili et al, 2003;Comellas et al, 2010) and membrane dynamics associated with inhibiting apoptosis and autophagy (Eisenberg-Lerner et al, 2009). However, too few downstream components have been defined to fully explain how the PI3K-PKB pathway regulates such membrane events, and ZNRF1 and ZNRF2 seemed attractive candidate mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include insulin-stimulated transport of GLUT4 glucose transporter-carrying vesicles to the plasma membrane to allow glucose to enter muscles and adipose tissues (Rowland et al, 2011;Taniguchi et al, 2006), increased cell surface expression of the Na + /K + ATPase to clear postprandial blood K + (Al-Khalili et al, 2003;Comellas et al, 2010) and membrane dynamics associated with inhibiting apoptosis and autophagy (Eisenberg-Lerner et al, 2009). However, too few downstream components have been defined to fully explain how the PI3K-PKB pathway regulates such membrane events, and ZNRF1 and ZNRF2 seemed attractive candidate mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The pump is also regulated acutely; for example the skeletal muscle Na + /K + ATPase activity is enhanced by insulin to clear blood K + after a meal, and by adrenaline and contraction to prevent fatigue (Ewart and Klip, 1995;Hatou et al, 2010). Demands for the Na + / K + ATPase also change markedly during nerve excitation, renal blood filtration and breathing, and Na + /K + ATPases are highly regulated in context-dependent ways by adrenaline, dopamine, thyroid hormone, aldosterone, catecholamines and insulin (reviewed by Comellas et al, 2010;Ewart and Klip, 1995). Mechanistic details of these regulations are sketchy, though protein kinases including PKA, PKC and SGK have been found to phosphorylate the a and FXYD subunits, triggering trafficking of the Na + /K + ATPase between intercellular membranes and cell surface, as well as changing intrinsic activity of the pump (Fuller et al, 2009;Han et al, 2010;Lang et al, 2010;Poulsen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Na,KATPase is composed of an a subunit that hydrolyzes ATP and exchanges intracellular Na + for extracellular K + , and a b subunit that controls enzyme assembly and insertion into the plasma membrane (15,50). Early studies showed AFC was increased by upregulation of Na,K-ATPase activity and facilitates the expression of Na,K-ATPase in alveolar cells (10,51). Analogously, our study demonstrates that RvD1 not only increases Na,K-ATPase a1 expression in rat lung tissues and primary ATII cells after LPS challenge by Western blotting, immunohistochemistry, and confocal laser-scanning microscopy measurement, but also upregulation of Na,K-ATPase activity in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,41 Recently, Comellas et al suggested that Rab 10 is implicated in sodium pump trafficking in response to insulin in pulmonary cells. 42 It will be important to identify the Rab protein involved in the AS160-mediated Na,K-ATPase trafficking in response to energy depletion, as well as the role of the GAP domain of AS160 in this process.…”
Section: Discussionmentioning
confidence: 99%